2006
DOI: 10.2527/jas.2005-614
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ractopamine and protein source on growth performance and carcass characteristics of feedlot heifers1

Abstract: An experiment was conducted to determine the relationship between feeding ractopamine and different amounts of MP on growth and carcass characteristics of feedlot heifers. Seventy-two crossbred heifers (475 kg of initial BW) were fed individually a diet based on steam-flaked corn for ad libitum intake for 29 d. Heifers were implanted with 140 mg of trenbolone acetate and 14 mg of estradiol-17beta 60 d before the experiment. Treatments were arranged as a 2 x 3 factorial and included 0 or 200 mg of ractopamine-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 14 publications
5
34
2
Order By: Relevance
“…Contrary to our hypothesis, increasing dietary CP above standard requirement had no effect on body gain or feed efficiency in the present study. Our results corroborate with that of Walker et al (2006), who suggested that feeding β-agonists could enhance the efficiency with which cattle use MP, thereby leading to no change in protein requirements.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Contrary to our hypothesis, increasing dietary CP above standard requirement had no effect on body gain or feed efficiency in the present study. Our results corroborate with that of Walker et al (2006), who suggested that feeding β-agonists could enhance the efficiency with which cattle use MP, thereby leading to no change in protein requirements.…”
Section: Discussionsupporting
confidence: 82%
“…The increase in the efficiency of AA metabolism by RH supplementation can also explain the increase in plasma total protein associated with the CP120 diet. A lower muscle degradation rate, because of RH supplementation, can lead to reduced plasma urea concentration (Walker et al, 2006;Bryant et al, 2012), but this was not the case in the present study. Plasma activities of the liver enzymes AST, GGT and ALP are used as possible indicators of hepatic disturbances.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Walker and Drouillard [39] also evaluated the impact of ractopamine hydrochloride on in vitro dry matter disappearance with isonitrogenous combinations of corn and soybean meal; corn and urea; or corn, soybean meal, and urea as substrates. There was an increase in in vitro dry matter digestibility with the addition of ractopamine hydrochloride (P < 0.001), and changes in dry matter disappearance (P < 0.01) were more pronounced when ractopamine was used in conjunction with more degradable forms of nitrogen (i.e., urea This could explain results of Walker [41] and Beermann [42], in which β-adrenergic agonists elicited a greater response in ruminants fed protein sources that were more readily degraded by ruminal microbes.…”
Section: Beta-adrenergic Agonists and Bacteriasupporting
confidence: 61%
“…Schroeder (2004) andWalker et al (2006) reported an improvement in HCW on steers treated with the PAA ractopamine. In addition, Plascencia et al (1999) obtained 13 kg increment in carcass weight for feedlot steers fed ZH.…”
Section: -30 G D-'mentioning
confidence: 99%